PENGARUH PENGAWASAN, LINGKUNGAN KERJA, FASILITAS KERJA TERHADAP PRESTASI KERJA PEGAWAI DINAS PANGAN DAN PERTANIAN KOTA TANJUNGBALAI - Azhari .; Widyaseno Trusyuwono; Rahwati .; Ahmad Zen; Siti Aminah Nasution (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation of the problem in this research is: How do the effects of supervision, work environment, work facilities on the work performance at Dinas Pangan Dan Pertanian Kota Tanjungbalai. This study aims to determine the effect of supervision, work environment, work facilities on employee performance. With a non probability sampling technique, the sample in this study was 38 people. The results showed; Partial supervision has a positive effect on employee work performance of 3,937; The work environment partially has a positive effect on employee work performance by 2,942; Work facilities partially have a positive effect on employee work performance of 3.507; Supervision, work environment and work facilities simultaneously have a positive and significant effect on employee work performance of 31.188.